2020
DOI: 10.1186/s13567-020-00859-w
|View full text |Cite
|
Sign up to set email alerts
|

Duck enteritis virus pUL47, as a late structural protein localized in the nucleus, mainly depends on residues 40 to 50 and 768 to 777 and inhibits IFN-β signalling by interacting with STAT1

Abstract: Duck enteritis virus (DEV) is a member of the Alphaherpesvirinae subfamily. The characteristics of some DEV genes have been reported. However, information regarding the DEV UL47 gene is limited. In this study, we identified the DEV UL47 gene encoding a late structural protein located in the nucleus of infected cells. We further found that two domains of DEV pUL47, amino acids (aa) 40 to 50 and 768 to 777, could function as nuclear localization sequence (NLS) to guide the nuclear localization of pUL47 and nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Our previous work has reported that DPV UL47 is mainly localized in the nucleus at the early stage of infection and diffused in the cytoplasm at the late stage of infection (He et al, 2020). To investigate the effects of US3 protein on UL47 localization in DPV infection, DEF cells were infected with CHv and US3 and the subcellular localization of UL47 was detected at 6 h post-infection (hpi) and 10 hpi.…”
Section: Us3 Promotes the Cytoplasmic Translocation Of Ul47 In Duck P...mentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous work has reported that DPV UL47 is mainly localized in the nucleus at the early stage of infection and diffused in the cytoplasm at the late stage of infection (He et al, 2020). To investigate the effects of US3 protein on UL47 localization in DPV infection, DEF cells were infected with CHv and US3 and the subcellular localization of UL47 was detected at 6 h post-infection (hpi) and 10 hpi.…”
Section: Us3 Promotes the Cytoplasmic Translocation Of Ul47 In Duck P...mentioning
confidence: 99%
“…Currently, a lot of work on DPV research has been completed in our laboratory ( Xin et al, 2009 ; Wu et al, 2012a , b ; He et al, 2020 ). It has been reported that the DPV US3 protein is essential for virus replication, and US3 deletion significantly reduced viral titer and the efficiency of infectious virion formation during DPV replication ( Deng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UL47 was found to be the most abundant tegument protein, present at ≥1250 copies per virion [ 18 ]. Similarly, UL47 has been identified as a component protein of extracellular virions [ 19 ]. Both gB and UL47 proteins are abundant antigens in mature virions and virus infected cell plasma membranes [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DPV is immunosuppressive and exhibits broad cell tropism [ 39 , 40 ]. While knowledge on the molecular mechanism of DPV immune evasion is limited, the UL47 protein is known to interact with signal transducer and activator of transcription 1 (STAT1) to inhibit duck IFN-β production [ 41 ]. In this study, we found that the DPV UL41 protein abrogated RIG-I/MDA5-mediated duck IFN-β production by downregulating the mRNA levels of important adaptors, and the conserved sites of the UL41 protein, E229, D231, and D232, were responsible for this activity.…”
Section: Introductionmentioning
confidence: 99%